(untitled) (Japan, 2017)
Contents: Estimation of biomass and carbon stock in young teak plantations in Thailand, Potential stereoscopic tree height measurement of teak plantations using Pléiades high-resolution satellite imagery, Effects of first thinning on growth and stem form of teak plantations in Thailand,...
Keywords: Forests and forestry,Rừng và lâm nghiệp; Thailand,Thái Lan